Seismic Risk Analysis of Government Buildings in the City of Tembilahan using FEMA P-58 - Rofriantona; Ridwan; Djauhari, Zulfikar (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Research in estimating losses and harm experienced by structures in the high seismic zone had been conducted in previous studies. Yet there is limited study carried out in low-moderate seismic areas. Therefore, an accurate method for calculating losses incurred due to earthquake events is needed in assessing the performance of building structures. This study aims to analyze the seismic risk of government buildings in Indragiri Hilir Regency Riau Province according to FEMA P-58. Seismic risk analysis was carried out on four reinforced concrete buildings. The four buildings reviewed in this study were categorized as low-rise buildings (Immigration Office) and medium-rise buildings (Regent's Office, Puri Husada Hospital, and Rusunawa). The buildings’ location according to SNI 1726-2019 was categorized as soft soil class. The results showed that the Immigration Office, Regent's Office, Puri Husada Hospital and Rusunawa were in a safe state. This is drawn by the value of the collapse probability in the current search condition, which is lower than the value of the collapse probability in the upper bound condition. Regent's Office and Rusunawa were the most vulnerable buildings where the value of the mean loss probability was the highest, namely 23.2%.